Montgomery's Federal Taxes (Book). - Gaa, Charles J.; Landman, J. H. (The Accounting Review, 1949)
Abstract Reviews the book "Montgomery's Federal Taxes," vol.1 and 2, "Corporations and Partnerships, 1948-49," by Robert H. Montgomery, Conrad B. Taylor and Mark E. Richardson and "Estates, Trusts and Gifts," by Robert H. Montgomery and James O. Wynn.